2022
DOI: 10.3389/fpubh.2022.923815
|View full text |Cite
|
Sign up to set email alerts
|

An update on the impact of SARS-CoV-2 pandemic public awareness on cancer patients' COVID-19 vaccine compliance: Outcomes and recommendations

Abstract: Background:Aside from the pandemic's negative health effects, the world was confronted with public confusion since proper communication and favorable decisions became an ongoing challenge. As a result, the public's perceptions were influenced by what they knew, the many sources of COVID-19 information, and how they interpreted it. With cancer patients continuing to oppose COVID-19 vaccines, we sought to investigate the COVID-19 pandemic and vaccine sources of this information in adult cancer patients, which ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
4
4
0
Order By: Relevance
“…In our study on cancer patients, 95% of the respondents were either Black or Hispanic, with 65% vaccinated and actively receiving treatment for their cancer during the crucial time of the initial rollout of COVID-19 vaccines in New York City. Overall, a large majority of our patients—79%—perceived that COVID-19 was risky and dangerous, and 65% considered the vaccines to be safe, similar to prior results in cancer patient studies [ 25 , 28 , 29 , 30 , 33 , 35 , 41 , 42 , 43 , 44 ]. Other self-reported reasons for being vaccinated stated by our participants included protecting themselves, family, and friends, the collective good of ending the pandemic, and trust in the vaccine and science; again, these were very similar to previous studies in cancer patients and ethnic minorities [ 23 , 25 , 28 , 29 , 31 , 35 , 50 ].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In our study on cancer patients, 95% of the respondents were either Black or Hispanic, with 65% vaccinated and actively receiving treatment for their cancer during the crucial time of the initial rollout of COVID-19 vaccines in New York City. Overall, a large majority of our patients—79%—perceived that COVID-19 was risky and dangerous, and 65% considered the vaccines to be safe, similar to prior results in cancer patient studies [ 25 , 28 , 29 , 30 , 33 , 35 , 41 , 42 , 43 , 44 ]. Other self-reported reasons for being vaccinated stated by our participants included protecting themselves, family, and friends, the collective good of ending the pandemic, and trust in the vaccine and science; again, these were very similar to previous studies in cancer patients and ethnic minorities [ 23 , 25 , 28 , 29 , 31 , 35 , 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…Another area of interest was to examine where patients received their information from, and the impact of their educational backgrounds. Our study demonstrated that participants encountered a wide range of sources of information, from television and radio to online sources such as the internet and social media, along with family and friends, similar to prior research [ 43 ]. Additionally, a positive predictor of vaccination uptake as seen previously was having access to information about COVID-19 vaccines [ 26 , 33 , 44 ], and trusting medical advice on vaccination [ 29 , 35 , 39 ].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations